Preliminary Assessment of Corbicula fluminea in Saiburi River, Southern Thailand - MOHAMAD SHAMSUL, ZAWEEN NAJJAH; RAK, AWENG EH; HAJI SAMAE, SUKREE; SYED OMAR, SHARIFAH AISYAH; AHMAD AFIP, LIYANA (Borneo Journal of Resource Science and Technology, 2017)
This study was conducted to determine the habitat characteristics and availability of existing C. fluminea in Saiburi River, which is in the southern part of Thailand. Saiburi River is one of the locations for C. fluminea harvesting in Southeast Thailand. In total, 329 individuals of C. fluminea were collected from Saiburi River by dragging the dredge using a clam dredge, approximately 1 m measured by the quadrat. The most abundant size found ranged between 11 and 20 mm in length with the highest density of 290 per m2 and mean density of 196 per m2. In this study, a total of seven physical, chemical and biological parameters (pH, temperature, dissolved oxygen, nitrate, phosphate, sediments and phytoplankton) were analyzed in five selected sampling points. The results for pH (6.7+0.15); temperature (34°C); dissolved oxygen (8.1+0.10 mg/L); nitrate (0.1+0.7 mg/L); phosphate (0.1+0.7 mg/L); sediments (loamy sand); phytoplanktons (29 species belong to 22 different families) were recorded. Therefore, the present report provides the information on the habitat of C. fluminea. Keywords: Corbicula fluminea, water quality, habitat, phytoplankton, Saiburi River